Interpersonal memory-based guidance of attention is reduced for ingroup members. - He, X; Lever, A; Humphreys, G (2011)
Participants jointly engaged in common tasks with co-actors can be influenced in guiding their own attention by representations of what the co-actor also holds in memory (He et al. under review). This demonstrates an effect of interpersonal memory on attention. Here, we tested how this interpersonal memory effect is affected by the relationship between the actors. Participants searched for targets while maintaining images in working memory or after previewed images that co-actors had to memorise. We examined three groups: Caucasian strangers (low ingroup relations) and two other groups with likely higher ingroup relations (Caucasian friends and Chinese participants living in Britain). In all three groups, attention was directed to stimuli that matched the item the individual had to memorise. However, images that had to be memorised by co-actors only attracted the attention of Caucasian strangers but not the Caucasian friends and Chinese participants. We suggest that interpersonal memory-based guidance of attention is modulated by the nature of the relationship between individuals and reduces when individuals have higher ingroup relations.